Enhancing Maternal Comfort: The Impact of Endorphin Massage Therapy on Reducing Preoperative Pain and Anxiety in Primigravida Mothers Undergoing Cesarean Section - Azissah RS, Danur; Rustandi, Handi; Nuh, Yalta Hasasnudin; Suyanto, Jipri (Journal of Current Health Sciences, 2024)
Pain and anxiety are significant challenges for primigravida mothers undergoing cesarean sections, with potential adverse effects on both maternal and neonatal outcomes. Endorphin massage therapy has emerged as a non-pharmacological intervention to mitigate these challenges by promoting the release of endorphins, which act as natural analgesics and anxiolytics. This study aimed to evaluate the effectiveness of endorphin massage therapy in reducing preoperative pain and anxiety levels in primigravida mothers scheduled for cesarean sections in Lubuklinggau, Indonesia. A quasi-experimental design was employed, involving 21 primigravida mothers divided into intervention and control groups. The intervention group received endorphin massage therapy, administered twice daily for three consecutive days prior to the cesarean section. Pain and anxiety levels were measured using the Numeric Rating Scale (NRS) and the Hamilton Anxiety Rating Scale (HARS), respectively. Statistical analyses were conducted to compare the pre- and post-intervention scores. The study found a significant reduction in both pain (mean difference: -4.3; 95% CI: -1.92 to -8.71; p < 0.001) and anxiety levels (mean difference: -8.3; 95% CI: -2.1 to -11.2; p < 0.001) in the intervention group compared to the control group. The reduction in anxiety was more pronounced than in pain, indicating the potent anxiolytic effect of endorphin massage therapy. Endorphin massage therapy significantly reduces preoperative pain and anxiety in primigravida mothers undergoing cesarean sections, particularly in alleviating anxiety. This non-pharmacological intervention could be a valuable addition to standard peripartum care, offering a safe, cost-effective alternative to pharmacological treatments. Further research with larger sample sizes is recommended to confirm these findings and explore long-term outcomes.